Melhorias no ensino ou inovações conservadoras? O que dizem educandos de diferentes gerações no contexto da EJA sobre os usos de TDIC? - Pedro Batela Neto (2019)
Although the Union, states and municipalities have been developing actions to foster the use of Digital Information and Communication Technologies (DICT) in basic education, recent studies show that this is not a widespread and systematized practice in Brazilian public schools, especially in the modality of Youth and Adult Education (YAE). In this context, it was investigated the relationships of popular learners of different generations, adolescents, young people and adults, who attend the YAE elementary school in a school of the municipal network of Contagem education, with the DICT inside and outside the school environment and their possible impacts on teaching and learning processes. The theoretical bases that support this work are aligned with the premises that: 1) YAE is a right that must be guaranteed and given to every citizen who has had access to education denied in other times of life; 2) this modality of education must incorporate and use the TDIC in a revolutionary and liberating way; 3) the school activities mediated by DICT must be dialogical; 4) the uses of DICT are not neutral. For the development of the research, it was carried out a bibliographic review on the subject, semi-structured interview and application of questionnaire with the students. The data obtained was analysed by qualitative methodological procedures. The results indicate that the DICT, even in a limited way, are present in the daily life of the students of the YAE and that their uses occur for different purposes, mainly entertainment. On the other hand, it was possible to verify that the subjects that attend this modality of education have the perception that such uses in the pedagogical practices can contribute to the construction of different knowledge, including school. In line with the research findings, the educational product was designed: "The Machines" in favour of a Social Quality Education, a Continuing Education Course for YAE educators on the didactic potential of the uses of DICT in pedagogical practices.